Supra Digastric Muscles Approach for Styloid Process Resection - Yokoya, Shigeomi (Journal of Neurological Surgery Part B: Skull Base, 2024)
Eagle syndrome, categorized into classical styloid syndrome and stylocarotid syndrome, presents challenges in determining the optimal surgical approach for styloid process (SP) resection. While intraoral resection suffices for many cases, especially classical styloid syndrome cases, stylocarotid syndrome sometimes demands a transcervical resection due to its intricate spatial dynamics. We describe a step-by-step procedure for modified transcervical resection using a supra digastric muscle approach (SDMA) for SP, emphasizing anatomical precision.The approach is described in the case of a 60-year-old woman with acute cerebral infarction from left internal carotid artery dissection. Employing carotid artery stenting, we identified SP elongation as the underlying cause requiring transcervical resection to avoid stent damage. The operative procedure involves meticulous dissection via a linear skin incision, exposing key anatomical structures such as the sternocleidomastoid muscles, digastric muscles (DMs), and the transverse process of the atlas. Surgical corridor via supra DM space is an invaluable technique, offering the shortest distance to the SP without compromising nearby nerves. The SP, covered by muscles and ligaments, is carefully stripped off, enabling its amputation near the temporal skull base. The entire procedure is performed under a microscope to preserve surrounding nerves.The SDMA is a simple and safe technique, offering enhanced anatomical precision and minimizing the risk of nerve damage.
Keywords: stylocarotid syndrome; elongated styloid process; transcervical resection; supra digastric muscle approach